2018
DOI: 10.20473/j.djmkg.v51.i4.p200-204
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting perceptions of male and female dental students regarding smile aesthetics based on their gingival display

Abstract: Background: Perception consists of personal opinion in relation to an object. In terms of aesthetics, perception normally differs from one individual to another based on several factors such as gender. When expressing emotion, a smile is the most important facial expression whose aesthetics are constructed from a number of components, including gingival display. Purpose: This study aimed to establish the comparative perceptions of the smile aesthetics of male and female dental students based on their gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These results are consistent with those of several recent studies on Chinese, 3 Jordanian, 4 and Indonesian populations. 6 , 7 , 8 In contrast, a study by Bolas-Colvee et al 9 using 250 evaluators aged around 19 years reported that the perceptions were affected by sex; however, the percentage of males and females was not equal, at 34.4% and 65.6%, respectively. Age was also one of the factors influencing the perception of an attractive smile because people of different ages had specific attitudes, lifestyles, and viewpoints.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with those of several recent studies on Chinese, 3 Jordanian, 4 and Indonesian populations. 6 , 7 , 8 In contrast, a study by Bolas-Colvee et al 9 using 250 evaluators aged around 19 years reported that the perceptions were affected by sex; however, the percentage of males and females was not equal, at 34.4% and 65.6%, respectively. Age was also one of the factors influencing the perception of an attractive smile because people of different ages had specific attitudes, lifestyles, and viewpoints.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that there was a significant difference in the perceptions of smile attractiveness between laypersons and specialists, males and females, and among laypersons of different ages. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 This information can help dentists understand how different subjects evaluate their smile. Once the treatment plan meets a subject's desires, dental treatment can be proceed smoothly.…”
Section: Introductionmentioning
confidence: 99%
“…16 An additional study conducted among dental students in Indonesia found that the most aesthetic smile was when the smile line covered the gingival zenith and only allowed visibility of the gingival embrasure. 33 However, participants in the study rated the smile with excessive gingival exposure as the least aesthetic and the smile line covering the gingival zenith and embrasure as the second least aesthetic. A direct comparison between the past study and the present could not be made as no measurement of the gingival display was conducted in millimeters.…”
Section: Ethnicitymentioning
confidence: 94%
“…With the development of science and research work domain 4,5 , the amount of waste, with bio-hazardous products, is also rising at an alarming rate, leading to instability of the ecosystem 6,7 . To reduce health problems and eradicate potential risks to people's health, the services of health care undoubtedly produce a massive amount of bio-medical waste, which creates elevated potentials for infection and injury 8 .…”
Section: Introductionmentioning
confidence: 99%